Sosialisasi Budidaya dan Pencegahan Serangan Virus Gemini pada Tanaman Cabai di Gapoktan Beken Jaya Desa Benai Keci Kabupaten Kuantan Singingi - Yunandra Yunandra; Julita Saidi; Dian Rakhmad; Dedi Mulyadi; Altop Amri Ya Habib; Rizki Oktavian; Elisa Apriliani; M. Joehari Jamili (Unri Conference Series: Community Engagement, 2025)
This community service program aims to improve farmers' knowledge and skills in cultivating chili plants and preventing geminivirus infection, a major constraint in production. The activity was carried out through outreach activities covering the stages of land cultivation, virus infection prevention techniques, whitefly population control as a vector, land clearing of weeds that are hosts of geminivirus, sanitation of infected plants, and proper pesticide use. In addition, participants were also introduced to the use of chili varieties resistant to the yellow geminivirus as an alternative sustainable solution. The results of the activity showed an increase in farmers' understanding of healthy cultivation strategies and integrated pest control, with an average score increasing from 45% to 85%, with the vector control aspect increasing from 30% to 90%. This outreach is expected to reduce the level of virus infection and increase chili productivity.